The CCDC43-ADRM1 axis regulated by YY1, promotes proliferation and metastasis of gastric cancer. (10th July 2020) - Wang, Jing; Wu, Xiaosheng; Dai, Weiyu; Li, Jiaying; Xiang, Li; Tang, Weimei; Lin, Jianjiao; Zhang, Wenjing; Liu, Guangnan; Yang, Qiong; Lin, Zhizhao; Sun, Yong; et al.
Abstract: Previous studies have shown an association between coiled-coil domain-containing (CCDC) genes and different cancers. Our previous studies revealed that CCDC43 is highly expressed in colorectal cancer, but the expression and molecular mechanisms of CCDC43 in gastric cancer (GC) are yet to be determined. Here, we show that CCDC43 is overexpressed in gastric tissues. CCDC43 expression is closely related to tumor differentiation, lymph-node-metastasis, and prognosis of gastric cancer. Overexpression of CCDC43 promotes the proliferation, invasion, and metastasis of GC cells. CCDC43 may upregulate and stabilize ADRM1, resulting in the construction of the ubiquitin-mediated proteasome. In contrast, inhibition of ADRM1 could reverse the function of CCDC43 in GC both in vitro and in vivo. Our data demonstrate that transcription factor YY1 directly binds to CCDC43 and ADRM1 gene promoters, leading to over-expression of CCDC43 and ADRM1. Furthermore, in vitro experiments demonstrate that knock down of CCDC43 or ADRM1 attenuates the YY1-mediated malignant phenotypes. Finally, the association among YY1, CCDC43 and ADRM1 is validated in clinical samples. Our findings suggest that the CCDC43-ADRM1 axis regulated by YY1, promotes proliferation and metastasis of GC, and the axis may be a potential therapeutic target for GC. Highlights: CCDC43 is overexpressed in gastric cancer (GC) and associated with prognosis in GC. CCDC43 promotes GC proliferation, invasion and metastasis. CCDC43 interaction with ADRM1 promotes proliferation, invasion and metastasis in GC. CCDC43 and ADRM1 are directly targeted by YY1 in GC cells.